1998
DOI: 10.1302/0301-620x.80b1.0800134
|View full text |Cite
|
Sign up to set email alerts
|

Subtalar arthrodesis with internal compression for post-traumatic arthritis

Abstract: We studied retrospectively the results in 24 patients (25 feet) who had been treated by subtalar arthrodesis with internal compression for post-traumatic arthritis from 1988 to 1992. Fifteen patients were men (16 feet) and nine (9 feet) were women. Their mean age was 43 years (22 to 68), and the average duration of follow-up was four years (2 to 6). A single compression screw was used in all feet and iliac-crest bone grafting in ten.Union was achieved in 24 of the 25 feet (96%). Based on a clinical scale the r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
15
0

Year Published

2003
2003
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 38 publications
(16 citation statements)
references
References 14 publications
1
15
0
Order By: Relevance
“…1,2,4,9,13,21 Besides painful subtalar arthritis secondary to joint incongruity, displaced calcaneal fractures may result in substantial hindfoot malalignment. While in situ arthrodesis has been reported to be successful in cases of isolated subtalar arthritis, 2,6,7,[22][23][24][25] gross depression and/or axial deviation of the calcaneum requires correction of calcaneal height and width as well as restoration of malalignment of the axial hindfoot. 2,5,8,10,25 Subtalar distraction bone-block arthrodesis was first described by Carr et al 8 and has been reported in several retrospective series since.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…1,2,4,9,13,21 Besides painful subtalar arthritis secondary to joint incongruity, displaced calcaneal fractures may result in substantial hindfoot malalignment. While in situ arthrodesis has been reported to be successful in cases of isolated subtalar arthritis, 2,6,7,[22][23][24][25] gross depression and/or axial deviation of the calcaneum requires correction of calcaneal height and width as well as restoration of malalignment of the axial hindfoot. 2,5,8,10,25 Subtalar distraction bone-block arthrodesis was first described by Carr et al 8 and has been reported in several retrospective series since.…”
Section: Discussionmentioning
confidence: 99%
“…This approach, puts the neurovascular structures at risk and may lead to anterior tibiotalar impingement at the head of the screw. 23 Since the eversion/inversion movement of the subtalar joint allows adaptation of the foot on uneven ground, the loss of shock absorption after subtalar fusion could have provoked pain beneath the screw heads in some of the patients although the heads were not prominent. Results of follow-up.…”
Section: Discussionmentioning
confidence: 99%
“…Advantages of it are said to be an easier initial approach, availability of the denser talar bone and a reduced risk of damage to the neurovascular bundle [2,6,10].…”
Section: Discussionmentioning
confidence: 99%
“…Achieving a secure bony fusion is also crucially dependant on mechanical factors, particularly compression and stability between the articular surfaces [6,7]. Therefore, the primary surgical goal is to secure early stability of the arthrodesis in order to encourage bony fusion in the desired anatomical position [6][7][8][9].…”
Section: Introductionmentioning
confidence: 99%
“…Its primary goal is pain-free weight bearing and stability of the hindfoot. After removal of the articular cartilage from the three facets, fixation can be achieved with one [1] or two screws [3] introduced from dorsal or plantar or with staples [4,7]. Addition of cancellous or cortical bone grafts is used, and, recently, bone substitutes are employed.…”
Section: Introductory Remarksmentioning
confidence: 99%